Strategic Leadership in Realizing Islamic Academic Culture in Muhammadiyah Universities: Systematic Literature Review - Ibnu Syakur Alsya'bani; Sadam Fajar Shodiq; Abd. Madjid (AL-ISHLAH: Jurnal Pendidikan, 2024)
Muhammadiyah ‘Aisyiyah Higher Education (PTMA) integrates the dimension of Al-Islam and Kemuhammadiyahan (AIK) into its educational framework, expanding the traditional “tri dharma” concept to include education, research, community service, and religious values. This study examines the role of strategic leadership in fostering an Islamic academic culture in alignment with Muhammadiyah’s vision. A Systematic Literature Review (SLR) approach was employed, analyzing 27 articles selected from 215 published between 2014-2024. The study involved keyword-based searches, stringent selection criteria, and thematic analysis for data visualization. Findings reveal that strategic leadership is pivotal in establishing an Islamic academic culture within PTMA. Key initiatives include implementing AIK-based policies, integrating Islamic values into curricula, and enhancing religious activities and facilities. These efforts have resulted in heightened motivation among the academic community, frequent religious engagement, and a campus atmosphere conducive to Islamic values. The study underscores the critical role of leadership in aligning institutional goals with the challenges of modernization, ensuring that Islamic values remain integral within the educational environment. This alignment supports the creation of a faith-based academic culture while addressing contemporary global demands. Strategic leadership significantly influences the development of Islamic culture in PTMA through policy, curriculum, and community engagement. These insights offer valuable guidance for other faith-based institutions aiming to sustain religious values in a modern educational context.